1988
DOI: 10.1111/j.1474-919x.1988.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity as a constraint affecting food and habitat choice of mussel‐feeding diving ducks

Abstract: Observations of freshwater drinking in Eiders feeding primarily on mussels led us to hypothesize that the highly saline sea water enclosed in mussels could cause salt‐related dehydration problems in the ducks, since they consume entire mussels. The proportion of sea water increases with increasing mussel size. Smaller duck species are more sensitive to the higher salt content of larger mussels than are larger ducks; however, salt stress may be avoided by feeding in habitats with lower salinity, by feeding on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…These results support empirically that the processes of developing and maintaining an active osmoregulatory machinery are energetically expensive (McArthur and Gorman, 1978;Burger and Gochfeld, 1984;Nyström and Pehrsson, 1988;Klaassen and Ens, 1990;Dosch, 1997). If the BMR is the sum of the metabolic rates of all the organs and tissues (Hulbert and Else, 2000;Turner et al, 2004), then the significant increase in BMR could be due to increased size and metabolic intensity of the organs and tissues involved in salt excretion.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…These results support empirically that the processes of developing and maintaining an active osmoregulatory machinery are energetically expensive (McArthur and Gorman, 1978;Burger and Gochfeld, 1984;Nyström and Pehrsson, 1988;Klaassen and Ens, 1990;Dosch, 1997). If the BMR is the sum of the metabolic rates of all the organs and tissues (Hulbert and Else, 2000;Turner et al, 2004), then the significant increase in BMR could be due to increased size and metabolic intensity of the organs and tissues involved in salt excretion.…”
Section: Discussionsupporting
confidence: 64%
“…Specifically, we predicted that when dunlins are relying on saltwater habitats they have higher BMRs than when they are relying on freshwater habitats. It has been suggested that the processes of developing and maintaining active salt glands are energetically expensive (McArthur and Gorman, 1978;Burger and Gochfeld, 1984;Nyström and Pehrsson, 1988;Klaassen and Ens, 1990;Dosch, 1997). On this basis, we also predicted that the dunlins' BMR in a saltwater regime would remain high until the birds were moved back to a freshwater regime.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Apart from the differences in hydroperiod, salinity is a major determinant of which plant and invertebrate food is available in each site (Espinar et al, 2002;Frisch et al, 2006b). In addition, consumption of prey originating from brackish water increases costs of osmoregulation (Nystrom and Pehrsson, 1988), and this may contribute to the preferential use of DNP by waterbirds.…”
Section: Speciesmentioning
confidence: 99%